Health system performance at the district level in Indonesia after decentralization - Choi Yoonjoung; Heywood Peter (BMC, 2010)
Abstract Background Assessments over the last two decades have showed an overall low level of performance of the health system in Indonesia with wide variation between districts. The reasons advanced for these low levels of performance include the low level of public funding for health and the lack of discretion for health system managers at the district level. When, in 2001, Indonesia implemented a radical decentralization and significantly increased the central transfer of funds to district governments it was widely expected that the performance of the health system would improve. This paper assesses the extent to which the performance of the health system has improved since decentralization. Methods We measured a set of indicators relevant to assessing changes in performance of the health system between two surveys in three areas: utilization of maternal antenatal and delivery care; immunization coverage; and contraceptive source and use. We also measured respondents' demographic characteristics and their living circumstances. These measurements were made in population-based surveys in 10 districts in 2002-03 and repeated in 2007 in the same 10 districts using the same instruments and sampling methods. Results The dominant providers of maternal and child health in these 10 districts are in the private sector. There was a significant decrease in birth deliveries at home, and a corresponding increase in deliveries in health facilities in 5 of the 10 districts, largely due to increased use of private facilities with little change in the already low use of public facilities. Overall, there was no improvement in vaccination of mothers and their children. Of those using modern contraceptive methods, the majority obtained them from the private sector in all districts. Conclusions There has been little improvement in the performance of the health system since decentralization occurred in 2001 even though there have also been significant increases in public funding for health. In fact, the decentralization has been limited in extent and structural problems make management of the system as a whole difficult. At the national level there has been no real attempt to envision the health system that Indonesia will need for the next 20 to 30 years or how the substantial public subsidy to this lightly regulated private system could be used in creative ways to stimulate innovation, mitigate market failures, improve equity and quality, and to enhance the performance of the system as a whole.